2011
DOI: 10.3390/polym3031151
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Crystal-to-Crystal Phase Transition in a Cadmium Halide Chain Polymer

Abstract: The chain polymer [{Cd(μ-X)2py2}1∞] (X = Cl, Br; py = pyridine) undergoes a fully reversible phase transition between a monoclinic low-temperature and an orthorhombic high-temperature phase. The transformation can be directly monitored in single crystals and can be confirmed for the bulk by powder diffraction. The transition temperature can be adjusted by tuning the composition of the mixed-halide phase: Transition temperatures between 175 K up to the decomposition of the material at ca. 350 K are accessible. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Crystals of 6 , albeit of good quality at ambient temperature, undergo a second‐order phase transition to monoclinic twins upon cooling; at temperatures above the phase transition, deformation density and thermal motion cannot be reliably deconvoluted. In agreement with the above observations, the second‐order phase transition temperature in mixed‐cation solids of the composition [Cd(μ‐Cl) 2– x (μ‐Br) x py 2 ] ∞ (0 < x < 2) is a function of the chemical composition 25,26. In contrast to these shortcomings encountered for 5 and 6 , excellent crystals were available for compound 7 ; it is isomorphous to 1 , 2 and 4 , the chain polymers with halide substituents in 3 and 5 position of the pyridine ligands.…”
Section: Resultssupporting
confidence: 84%
“…Crystals of 6 , albeit of good quality at ambient temperature, undergo a second‐order phase transition to monoclinic twins upon cooling; at temperatures above the phase transition, deformation density and thermal motion cannot be reliably deconvoluted. In agreement with the above observations, the second‐order phase transition temperature in mixed‐cation solids of the composition [Cd(μ‐Cl) 2– x (μ‐Br) x py 2 ] ∞ (0 < x < 2) is a function of the chemical composition 25,26. In contrast to these shortcomings encountered for 5 and 6 , excellent crystals were available for compound 7 ; it is isomorphous to 1 , 2 and 4 , the chain polymers with halide substituents in 3 and 5 position of the pyridine ligands.…”
Section: Resultssupporting
confidence: 84%
“…An Oxford Cryosystems 700 controller was used to ensure constant temperature during data collection. Previous work on phase transitions conducted in parallel on single crystals and on powder at 120 K (Hu & Englert, 2005), at 207 K (Hu et al, 2003) and over the temperature range 175-325 K (Lamberts et al, 2011) indicated a reproducibility of better than 2 K and a temperature match of better than 5 K with alternative cooling devices. Frames were collected in !-scan mode in nine runs with different settings for detector angle and crystal rotation ' and integrated with the help of the program SAINT (Bruker, 2003).…”
Section: Diffraction Experiments On (1)mentioning
confidence: 97%
“…We have investigated the structural chemistry of the reaction products of manganese halides with racemic and enantiopure proline and highlighted the role of chirality for the solid-state structures of the products (Lamberts & Englert, 2012). Additionally we have shown that a solid-state property such as the temperature for a certain phase transition may be tuned by isomorphous replacement (Lamberts et al, 2011), similar to the situation in classical inorganic salts. In this contribution we address the structural chemistry of racemic and enantiopure alanine derivatives of metal halides, both for the alkaline earth cation Ca II and the transition metal ion Mn II .…”
Section: Introductionmentioning
confidence: 93%